Influence on Uranium(VI) migration in soil by iron and manganese salts of humic acid: Mechanism and behavior. (January 2020) - Zhang, Yuan-yuan; Lv, Jun-wen; Dong, Xue-jie; Fang, Qi; Tan, Wen-fa; Wu, Xiao-yan; Deng, Qin-wen
Abstract: Soil contains large amounts of humic acid (HA), iron ions and manganese ions, all of which affect U(VI) migration in the soil. HA interacts with iron and manganese ions to form HA salts (called HA-Fe and HA-Mn in this paper); however, the effects of HA-Fe and HA-Mn on the migration of U(VI) is not fully understood. In this study, HA-Fe and HA-Mn were compounded by HA interactions with ferric chloride hexahydrate and manganese chloride tetrahydrate, respectively. The influence of HA, HA-Fe and HA-Mn on U(VI) immobilization and migration was investigated by bath adsorption experiments and adsorption-desorption experiments using soil columns. The results showed that the presence of HA, HA-Fe and HA-Mn retarded the migration of U(VI) in soil. Supported by X-ray photoelectron spectroscopy (XPS) and BCR sequential extraction analyses, a plausible explanation for the retardation was that HA-Fe and HA-Mn could reduce hexavalent uranium to stable tetravalent uranium and increase the specific gravity of Fe/Mn oxide-bound uranium and organic/sulfide-bound uranium, which made it difficult for them to longitudinally migrate in soil. Scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and surface area and pore size analyses indicated that the complex formed between the hydroxyl, amino and carboxyl groups of HA-Fe and U(VI) increased the crystallinity of HA-Fe. The reaction between U(VI) and the hydroxyl, amino, aldehyde, keto and chlorine-containing groups of HA-Mn had no effect on the crystallinity of HA-Mn. Notably, the column desorption experiment found that the U(VI) immobilized in the soil remigrated under the effect of rain leaching, and acid rain promoted uranium remigration better than neutral rain. The findings provide some guidance for the decommissioning disposal of uranium contaminated site and it's risk assessments. Graphical abstract: Image 1